2019
DOI: 10.1093/brain/awz059
|View full text |Cite
|
Sign up to set email alerts
|

Scalp recorded spike ripples predict seizure risk in childhood epilepsy better than spikes

Abstract: In the past decade, brief bursts of fast oscillations in the ripple range have been identified in the scalp EEG as a promising non-invasive biomarker for epilepsy. However, investigation and clinical application of this biomarker have been limited because standard approaches to identify these brief, low amplitude events are difficult, time consuming, and subjective. Recent studies have demonstrated that ripples co-occurring with epileptiform discharges (‘spike ripple events’) are easier to detect than ripples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 65 publications
4
77
1
Order By: Relevance
“…Such a correlation was not found for interictal spikes, ripples, or ripples co-occurring with spikes (IES-ripples). These findings are in line with previous work suggesting that HFOs might identify epileptogenic tissue better than spikes (9,34). It is still subject to debate which of the HFO subgroups is suited best as a biomarker, but a popular notion is that ripples lack specificity, possibly because some of the events are physiological.…”
Section: Association Between Interictal Fast Ripples and Seizure-genesupporting
confidence: 90%
“…Such a correlation was not found for interictal spikes, ripples, or ripples co-occurring with spikes (IES-ripples). These findings are in line with previous work suggesting that HFOs might identify epileptogenic tissue better than spikes (9,34). It is still subject to debate which of the HFO subgroups is suited best as a biomarker, but a popular notion is that ripples lack specificity, possibly because some of the events are physiological.…”
Section: Association Between Interictal Fast Ripples and Seizure-genesupporting
confidence: 90%
“…Our external validation shows that the discrimination of the Lamberink 5‐year model is adequate (AUC = 0.68, 95% CI = 0.60‐0.76), but the model significantly overestimated the risk of seizure recurrence (Figure ). To improve the prediction model, additional possibly meaningful predictors should be identified and added to the model, such as scalp‐recorded spike ripples, risk marker alleles, and even individual brain structure . Moreover, in theory, prediction models of epilepsy should be developed into several parts according to different epilepsy syndromes, because epilepsy is a highly heterogeneous disease and different epilepsy syndromes have entirely distinct prognoses .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence showed that HFOs below 250 Hz (ripples) can be seen on scalp EEG [10][11][12][13][14][15][16][17] and magnetoencephalography [18][19][20][21][22][23][24][25][26][27] (MEG) recordings, despite the small extent of their cortical generators. 11,16,28 Yet, their translation to clinical practice is still limited.…”
Section: Introductionmentioning
confidence: 99%